Desechos generados en ganadería bovina y su impacto en el medio ambiente del sector sur del Cantón Quevedo - Novillo Célleri, Johnny Enrique (2016)
A descriptive study related to waste generated on farms settled in the southern part of the cantón Quevedo, Ecuador was made; these farms have 14 years of operation and have been operating without any technical control framework and environmental preservation. The objective was to determine the impact of the waste generated in these farms and the impact on the environment of the environment. To identify the wastes generated a survey was conducted to 40 producers who performed the analysis by visual description of the physical, chemical and biological wastewater characteristics. The description of the characteristics of livestock activity was carried out by observation technique, for it five farms were chosen, they were visited on several occasions to obtain the necessary information, while environmental impacts were identified through the matrix Leopold, analysis of pH, temperature, electrical conductivity, total solids, volatile solids and volatile solids not performed. The results show that the inhabitants considered major pollutants feces (45%) and odors (35%), and there is no proper disposal of manure; St. Augustine ranch only piles up and then placed in pastures by cattle manure, water, untreated, it seeps into the soil and consequently contaminates. Regarding the assessment of environmental impacts using the Leopold matrix it was obtained as relevant observations on the aggregation of impacts as follows: It affects soil compaction components, direct destruction and instability of slopes; it affects the wildlife component invertebrates; and scenic beauty in natural and artificial components. Chemical analysis showed that wastewater St. Augustine ranch has the highest content of pollutants. In this regard it is recommended to livestock producers friendly practices incorporate environment.